Public responses to the Salisbury Novichok incident: a cross-sectional survey of anxiety, anger, uncertainty, perceived risk and avoidance behaviour in the local community. Issue 9 (25th September 2020) - Rubin, G James; Webster, Rebecca; Amlot, Richard; Carter, Holly; Weston, Dale; Wessely, Simon
Abstract : Objectives: Malicious incidents involving chemical agents sometimes trigger high public concern. We aimed to (1) identify levels of emotion, perceived risk and behaviour change with regard to visiting Salisbury, 1 month after three people were poisoned with a nerve agent; and (2) test whether factors including receipt of information, beliefs about personal exposure and trust in government were associated with these outcomes. Design: A cross-sectional telephone survey of a random sample of Salisbury residents. Setting: Conducted between 5 and 13 April 2018. Participants: 500 residents aged 18 or over. Outcome measures: Self-reported anxiety, anger, uncertainty, perceived risk to self and avoidance of Salisbury. Results: Any degree of anxiety, anger and uncertainty was reported by 40.6%, 29.8% and 30.6% of participants, respectively. For the majority, the level of emotion reported was mild. Only 7.0% met the criteria for high anxiety and 5.2% reported feeling any risk to their health, whereas 18.6% reported avoiding Salisbury. Factors associated with avoidance of Salisbury included being female, unable to rule out exposure for oneself or of loved ones, believing the incident was targeted against the general public, and lower trust in the government and responding agencies. Hearing a lot or a little about the recovery support (eg, financial packages), as opposed to nothing at all, and being satisfied with this information were associated with reduced avoidance. Conclusions: Although the March 2018 Salisbury incident had a relatively modest impact on emotion and risk perception in the community, the number who reported avoiding the city was notable. In this, and in future incidents, assuring people that contamination resulted from a targeted, rather than indiscriminate, incident; demonstrating that contamination is contained within specific areas; improving communication about any financial support; and promoting trust in responding agencies should help provide additional reassurance to the community.